2016
DOI: 10.1007/s11164-016-2605-9
|View full text |Cite
|
Sign up to set email alerts
|

Practical synthesis of 2-(4-benzyl-piperazin-1-ylmethyl)-5, 6-dimethoxy-3-methyl-[1, 4]benzoquinone hydrochloride

Abstract: The title compound was readily prepared from 2, 3, 4, 5-tetramethoxytoluene via the Blanc reaction, oxidation, and alkylation. The described method provides a good yield of the heterocyclic substitute at the C-5 position of the Coenzyme Q homologue and is suitable for the synthesis of other homologues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Compound 3a , 7 red oil, 85% yield . 1 H NMR (500 MHz, CDCl 3 ): δ 4.29 (s, 2H, C H 2 Cl), 3.88 (s, 3H, OC H 3 ), 3.86 (s, 3H, OC H 3 ), 1.99 (s, 3H, C H 3 ); 13 C NMR (101 MHz, CDCl 3 ): 183.7 (C=O), 181.6 (C=O), 144.7, 144.2, 142.3, 136.7, 61.2 (O C H 3 ), 61.1 (O C H 3 ), 35.0 ( C H 2 Cl), 11.8 ( C H 3 ); mass spectrometry (MS; electrospray ionization (ESI)): m/z = 253 [M + Na] + .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3a , 7 red oil, 85% yield . 1 H NMR (500 MHz, CDCl 3 ): δ 4.29 (s, 2H, C H 2 Cl), 3.88 (s, 3H, OC H 3 ), 3.86 (s, 3H, OC H 3 ), 1.99 (s, 3H, C H 3 ); 13 C NMR (101 MHz, CDCl 3 ): 183.7 (C=O), 181.6 (C=O), 144.7, 144.2, 142.3, 136.7, 61.2 (O C H 3 ), 61.1 (O C H 3 ), 35.0 ( C H 2 Cl), 11.8 ( C H 3 ); mass spectrometry (MS; electrospray ionization (ESI)): m/z = 253 [M + Na] + .…”
Section: Methodsmentioning
confidence: 99%
“…4 Among the published syntheses of CoQ 10 , Lipshutz et al 5 and Negishi et al 6 developed efficient procedures based on metal-catalyzed cross-coupling between a chloromethyl-CoQ 0 (compound 3a, Figure 1) and organoaluminum or organozinc reagents. In our previous study, 7 we found N-heterocyclic-substituted coenzyme Q compounds which exhibited good biological activities. 8 There are several methods reported for the synthesis of alkyl-CoQ 0 .…”
Section: Introductionmentioning
confidence: 95%
“…Most of the methods used CoQ 0 as starting material, compound 3 was obtained by reaction with toxic bromine [10], and few syntheses leading to compound 3 have been disclosed [11]. Hence, based on our previous work on the synthesis of CoQ analogues [12][13][14][15][16], we now report an efficient synthetic path for compound 3 as shown in Scheme 2. The reaction is operationally simple and could be used in the preparation of other coenzyme Q analogues.…”
Section: Introductionmentioning
confidence: 99%